A Turkish Alexander? Michael Attaleiates, Porus, and Alexander The Great - Mallan, Christopher (Histos, 2017)
This short note discusses Michael Attaleiates' account of the encounter between prince Liparites and the Turk, Tughril Beg (Attal. 8.2 [Bekker p. 45 = Pérez Martín p. 34]), which contains an allusion to the famous exchange between Alexander the Great and Porus.